Mitigating barriers against accessible cities and transportation, for child-rearing households. (March 2015) - Ohmori, Nobuaki
Abstract: This paper discusses the types of cities and transportation environments required for increasing quality of life of child-rearing households in Japan. The author proposes a classification of barriers that child-rearing parents face in their daily lives. An international comparative study shows that the behavior of and public attitudes toward stroller users in Japan are very different from those in other countries. In addition to providing accessible environments in cities and transportation systems, improving the quantity and quality of childcare services and information, and alleviating the scheduling constraints that come along with rearing children, it is also essential to raise public awareness of child rearing and travelers with children, a development that could help increase the birth rate in Japan. Highlights: Classification of barriers that parents with young children face in their daily lives is proposed from an activity-based travel analysis approach. Behavior of and public attitudes toward stroller users in Japan are very different from other countries. Raising public awareness of child-rearing is very important to realize accessible cities and transportation for child-rearing households in Japan.